What do we need to consider when planning, implementing and researching the use of alternatives to face-to-face consultations in primary healthcare? - Atherton, H; Ziebland, S (SAGE Publications, 2016)
Objectives Communications technologies are variably utilised in healthcare. Policymakers globally have espoused the potential benefits of alternatives to face-to-face consultations, but research is in its infancy. The aim of this essay is to provide thinking tools for policymakers, practitioners and researchers who are involved in planning, implementing and evaluating alternative forms of consultation in primary care. Methods We draw on preparations for a focussed ethnographic study being conducted in eight general practice settings in the UK, knowledge of the literature, qualitative social science and Cochrane reviews. In this essay we consider different types of patients, and also reflect on how the work, practice and professional identities of different members of staff in primary care might be affected. Results Elements of practice are inevitably lost when consultations are no longer face-to-face, and we know little about the impact on core aspects of the primary care relationship. Resistance to change is normal and concerns about the introduction of alternative methods of consultation are often expressed using proxy reasons; for example, concerns about patient safety. Any planning or research in the field of new technologies should be attuned to the potential for unintended consequences. Conclusions Implementation of alternatives to the face-to-face consultation is more likely to succeed if approached as co-designed initiatives that start with the least controversial and most promising changes for the practice. Researchers and evaluators should explore actual experiences of the different consultation types amongst patients and the primary care team rather than hypothetical perspectives.